Exploring slime mould diversity in high‐altitude forests and grasslands by environmental RNA analysis. Issue 1 (17th December 2012) - Kamono, Akiko; Meyer, Marianne; Cavalier‐Smith, Thomas; Fukui, Manabu; Fiore‐Donno, Anna Maria
Abstract In spite of the ecological importance of protists, very little data is available on their distribution in soil. This investigation is the first of its kind on what could be the major components of the soil protistan community, the Myxomycetes, or plasmodial slime‐moulds, a monophyletic class in the phylum Amoebozoa. Myxomycetes have a complex life cycle culminating in the formation of mainly macroscopic fruiting bodies, highly variable in shape and colour, which can be found in every terrestrial biome. Despite their prevalence, they are paradoxically absent from environmental DNA sampling studies. We obtained myxomycete SSU rRNA gene sequences from soil‐extracted RNAs using specific primers. Soil samples were collected in three mountain ranges (France, Scotland and Japan). Our study revealed an unexpectedly high diversity of dark‐spored Myxomycetes, with the recovery of 74 phylotypes. Of these, 74% had < 98% identity with known sequences, showing a hidden diversity; there was little overlap between localities, implying biogeographical patterns. Few phylotypes were dominant and many were unique, consistent with the 'rare biosphere' phenomenon. Our study provides the first detailed insight into the community composition of this ecologically important group of protists, establishing means for future studies of their distribution, abundance and ecology.